IDENTIFIKASI KOMPETENSI DAN PERFORMANSI DALAM KARANGAN BERBAHASA JEPANG - Umul Khasanah; Khaira Imandiena Bahalwan; Novi Andari (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2019)
The knowledge and skills acquired or studied are a competency possessed by a learner. Competence refers to a person's basic knowledge of a system, event, or fact, which is an unobservable ability to do and display something. While performance is a concrete manifestation and can be observed or realized on a competency. This research was conducted to determine how much performance shown by Japanese language students in Japanese Literature Study Program Untag Surabaya in the sixth semester in using Japanese sentence pattern learning material in an essay. Students of Japanese Literature Study Program Untag Surabaya in the sixth semester took the Sakubun II course (Writing Level II / Intermediate). The choice of words and sentence patterns in the essays produced were compared with the number of Japanese sentence patterns they had learned. The research method used is an observation method with a qualitative descriptive approach. The results of the study stated that 1) the sentences produced in the essay used a sentence pattern that was lower than the number of sentence patterns that had been studied; 2) found sentence patterns that were not taught through required textbooks, it was alleged that students used sentence patterns they learned from other textbooks, internet, anime, mangoes, and from other sources; 3) students use sentence patterns that are adjusted to the level of writing in the Sakubun II course.